Geriatric nutritional risk index as an independent predictor of 1-year mortality in elderly patients with hip fractures - Cengizhan Kurt; Sercan Capkin; Ali Ihsan Kilic; Hakan Cici; Mehmet Akdemir (PLoS ONE, 2026)
Background Hip fractures are a major cause of morbidity and mortality in the elderly, with 1-year mortality rates up to 40%. Malnutrition is a key determinant of adverse outcomes. The Geriatric Nutritional Risk Index (GNRI), based on serum albumin and body weight, is a simple nutritional tool. This study investigated whether GNRI independently predicts 1-year mortality after hip fracture surgery beyond conventional risk factors. Methods We retrospectively analyzed 624 patients aged ≥65 years who underwent hip fracture surgery at two tertiary centers. Demographic, clinical, and perioperative data were collected. GNRI was calculated for all patients. Independent predictors of mortality were identified using logistic regression, and ROC analysis determined the optimal GNRI cut-off. Results The 1-year mortality rate was 22.3%. In univariate analysis, older age, ASA class III–IV, low albumin, low GNRI, and multiple comorbidities were significantly associated with mortality. Each 0.1 g/dL increase in albumin was associated with 26% lower odds of 1-year mortality, and each 1-point increase in GNRI was associated with 25.5% lower odds of mortality (p < 0.001). In multivariate analysis, only age, ASA classification, and GNRI remained independent predictors. ROC analysis showed excellent discrimination for GNRI (AUC: 0.928), with a cut-off of 91.45 (sensitivity 87.8%, specificity 90.3%). Patients with GNRI ≤91.45 had a markedly higher 1-year mortality (72.2% vs. 3.7%; RR: 19.32, 95% CI: 12.01–31.09). Conclusions GNRI independently predicted 1-year mortality in elderly hip fracture patients. A GNRI ≤91.45 was associated with a 19-fold higher risk, while higher scores had a protective effect, underscoring GNRI as a practical tool for perioperative risk stratification.